COVID-19 and COPD: a narrative review of the basic science and clinical outcomes. (4th November 2020) - Higham, Andrew; Mathioudakis, Alexander; Vestbo, Jørgen; Singh, Dave
The 2019 coronavirus disease (COVID-19) pandemic is caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). Clinical outcomes, including mortality, are worse in males, older individuals and patients with comorbidities. COPD patients are included in shielding strategies due to their susceptibility to virus-induced exacerbations, compromised pulmonary function and high prevalence of associated comorbidities. Using evidence from basic science and cohort studies, this review addresses key questions concerning COVID-19 and COPD. First, are there mechanisms by which COPD patients are more susceptible to SARS-CoV-2 infection? Secondly, do inhaled corticosteroids offer protection against COVID-19? And, thirdly, what is the evidence regarding clinical outcomes from COVID-19 in COPD patients? This up-to-date review tackles some of the key issues which have significant impact on the long-term outlook for COPD patients in the context of COVID-19. This up-to-date review tackles some of the key issues which have significant impact on the long-term outlook for COPD patients in the context of COVID-19 https://bit.ly/36PKzEO